Influence Dividend Policy and Earning Per Share on Company Value in Food Sub Sector Companies and Listed Drinks on Bursa Efek Indonesia - Lidya Natalia; Agus Tripriyono (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This research aims to prove the influence of Dividend Policy and earnings per Share (EPS) on Company Value in Food and Beverage Companies listed on the Indonesia Stock Exchange (BEI) from 2016 to 2020. The type of data in this research process is quantitative where the data is obtained from financial reports. The population used in this research was 7 companies multiplied by 5 years, namely 35 observations. In this research, the method used is panel data regression, using the Chow test, Hausman test, and Lagrange test Multiplier and Common models Effect is the best model to use in this research. The research results show that the Dividend Policy (X1) does not have a significant effect on company value partially on Company Value (Y) and the Earning Per Share (EPS) variable has a partially significant positive effect on Company Value (Y). Company value is the company's performance as reflected by the share price which is formed by demand and supply in the capital market which reflects the public's assessment of the company's performance.